Variations in decay resistance of cryptomeria fortunei - Xiaoping, Li; Chunli, Li; Morrell, Jeffrey J.; Haishan, He; Jian, Qiu; Neng, Zhang (Maderas. Ciencia y Tecnología, 2023)
Cryptomeria fortunei has been widely planted in many cities in southern China. Eventually some of this material may be utilized for timber, but there are relatively few studies of durability of this resource. There is also some question as to whether Cryptomeria fortunei is a synonym for Cryptomeria japonica or Japanese cedar (Sugi). Evaluating the durability of the Chinese resource will help ensure that the decay resistance of this urban plantation resource is properly categorized. The decay resistance of Cryptomeria fortunei wood was assessed in soil block and agar block tests against Trametes versicolor, Gloeophyllum trabeum and Rhodonia placenta. Hot water and ethanol extractive contents of the heartwood were determined on sections from various distances above ground and then FTIR spectroscopy was used to characterize the wood before and after fungal exposure. Weight losses in sapwood were consistent with the minimal decay resistance of this portion of the wood. Inner and outer heartwood weight losses were more variable suggesting that the heartwood of this species would be considered to be only moderately durable. Extractives were weakly correlated with decay resistance. FTIR results were more variable, although they suggested heavier attack of lignin components by the brown rot fungi. The results suggest that Cryptomeria fortunei would need to be protected from the weather unless supplemental preservative treatments were applied.